Computer Vision - ACCV 2012 Workshops ACCV 2012 International Workshops, Daejeon, Korea, November 5-6, 2012, Revised Selected Papers, Part II - Park, Jong-Il.; Kim, Junmo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The two volume set, consisting of LNCS 7728 and 7729, contains the carefully reviewed and selected papers presented at the nine workshops that were held in conjunction with the 11th Asian Conference on Computer Vision, ACCV 2012, in Daejeon, South Korea, in November 2012. From a total of 310 papers submitted, 78 were selected for presentation. LNCS 7728 contains the papers selected for the International Workshop on Computer Vision with Local Binary Pattern Variants, the Workshop on Computational Photography and Low-Level Vision, the Workshop on Developer-Centered Computer Vision, and the Workshop on Background Models Challenge. LNCS 7729 contains the papers selected for the Workshop on e-Heritage, the Workshop on Color Depth Fusion in Computer Vision, the Workshop on Face Analysis, the Workshop on Detection and Tracking in Challenging Environments, and the International Workshop on Intelligent Mobile Vision.
Historical Document Binarization Based on Phase Information of Images -- Can Modern Technologies Defeat Nazi Censorship? -- Coarse-to-Fine Correspondence Search for Classifying Ancient Coins -- Archiving Mural Paintings Using an Ontology Based Approach -- Robust Image Deblurring Using Hyper Laplacian Model -- SVD Based Automatic Detection of Target Regions for Image Inpainting -- Presentation of Japanese Cultural Event Using Virtual Reality -- High-Resolution and Multi-spectral Capturing for Digital Archiving of Large 3D Woven Cultural Artifacts -- Exploring High-Level Plane Primitives for Indoor 3D Reconstruction with a Hand-held RGB-D Camera -- A Fusion Framework of Stereo Vision and Kinect for High-Quality Dense Depth Maps -- Robust Fall Detection by Combining 3D Data and Fuzzy Logic -- KinectAvatar: Fully Automatic Body Capture Using a Single Kinect -- Essential Body-Joint and Atomic Action Detection for Human Activity -- Recognition Using Longest Common Subsequence Algorithm -- Exploiting Depth and Intensity Information for Head Pose Estimation with Random Forests and Tensor Models -- Dynamic Hand Shape Manifold Embedding and Tracking from Depth Maps -- View-Invariant Object Detection by Matching 3D Contours -- Human Detection with Occlusion Handling by Over-Segmentation and Clustering on Foreground Regions -- Spin Image Revisited: Fast Candidate Selection Using Outlier Forest Search -- MRF Guided Anisotropic Depth Diffusion for Kinect Range Image Enhancement -- A Priori-Driven PCA -- The Face Speaks: Contextual and Temporal Sensitivity to Backchannel Responses -- Virtual View Generation Using Clustering Based Local View Transition Model -- 3D Facial Expression Synthesis from a Single Image Using a Model Set -- Face Hallucination on Personal Photo Albums -- Techniques for Mimicry and Identity Blending Using Morph Space PCA -- Facial and Vocal Cues in Perceptions of Trustworthiness -- Disagreement-Based Multi-system Tracking -- Monocular Pedestrian Tracking from a Moving Vehicle -- Tracking the Untrackable : How to Track When Your Object Is Featureless -- A Robust Particle Tracker via Markov Chain Monte Carlo Posterior Sampling -- A Framework for Inter-camera Association of Multi-target Trajectories by Invariant Target Models -- Colour Descriptors for Tracking in Spatial Augmented Reality -- Covariance Descriptor Multiple Object Tracking and Re-identification with Colorspace Evaluation -- Iterative Hypothesis Testing for Multi-object Tracking with Noisy/Missing Appearance Features -- Novel Adaptive Eye Detection and Tracking for Challenging Lighting Conditions -- Obstacles Extraction Using a Moving Camera -- Scene Text Detection and Tracking for a Camera-Equipped Wearable Reading Assistant for the Blind -- Object Tracking across Non-overlapping Cameras Using Adaptive Models -- Combining Fast Extracted Edge Descriptors and Feature Sharing for Rapid Object Detection -- Motion Segmentation by Velocity Clustering with Estimation of Subspace Dimension -- Beyond Spatial Pyramid Matching: Spatial Soft Voting for Image Classification -- Efficient Geometric Re-ranking for Mobile Visual Search -- Intelligent Photographing Interface with On-Device Aesthetic Quality Assessment -- Camera Pose Estimation of a Smartphone at a Field without Interest Points -- Hierarchical Scan-Line Dynamic Programming for Optical Flow Using Semi-global Matching Novel Multi-view Synthesis from a Stereo Image Pair for 3D Display on Mobile Phone -- An Accurate Method for Line Detection and Manhattan Frame Estimation -- Hierarchical Stereo Matching Based on Image Bit-Plane Slicing.
Keywords: Computer science; Computer vision; Geometry; Computer Science; Computer Imaging, Vision, Pattern Recognition and Graphics; User Interfaces and Human Computer Interaction; Media Design; Geometry